Ultratone therapy for the complex treatment of localized scleroderma - N. V. Sorokina; M. M. Tlish (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The examination and treatment of 48 patients with circumscribed scleroderma were conducted. Two groups of these patients were formed with method of adaptive randomization. In the control group complex treatment underwent according to the standards in this nosology. In the study one, we conducted ultratonotherapy. The course of treatment was 21 days in both groups. Treatment results were evaluated in accordance with the dynamics of cutaneous pathological process and microcirculation in the area of lesions. In the process of treatment positive clinical dynamics appeared in the study group earlier and were accompanied by increased blood flow. The results indicate that ultrasonotherapy increases the efficiency and reduces the treatment time of patients with circuscrimbed scleroderma.